Gwarancje wolności sumienia i religii w Konstytucji Rzeczypospolitej Polskiej z dnia 2 kwietnia 1997 r. - Gołębiowska, Anna (Prawo Kanoniczne, 2011)
The systemic transformation initiated by the Roundtable talks of 1989 made it necessary for Poland to amend its constitution, including the regulations concerning the freedom of conscience and religion. Reflecting only the Catholic Church’s official positions, presents issues concerning the Catholic Church’s position on religious freedom in the individual dimension, that is, the freedom of conscience and religion. The Conference of the Polish Episcopate’s 1990-1997 positions on religious freedom in the individual dimensions contained some of the most important aspects of the teaching of the Second Vatican Council. The constitutional guarantees of religious freedom contained in the article 53 – freedom of conscience and religion – should be seen as a compromise between the principles of liberal ideology and the teachings of the Second Vatican Council. Debate’s counterparts were: the President of the Polish Republic, the Constitutional Commission of the National Assembly, the Constitutional Commissions of the two chambers of Polish Parliament: political Parties and citizens’ movements as well as individual persons. More then that, as far as this freedom touches the crucial element of the human nature, it creates in every person a deep foundation for the existence of other freedoms.